2016
DOI: 10.1111/ijfs.13130
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin I‐converting enzyme inhibitory peptides FQPSF and LKYPI identified in Bacillus subtilis A26 hydrolysate of thornback ray muscle

Abstract: Summary Angiotensin I‐converting enzyme (ACE) inhibitory peptides have been searched in thornback ray (Raja clavata) muscle hydrolysed with Bacillus subtilis A26 proteases until a hydrolysis degree of 18.35%. The hydrolysate showed an IC50 of 0.83 mg mL−1. To identify peptides responsible for this activity, the extract was eluted through size‐exclusion chromatography and fractions collected. The highest ACE inhibitory activity was found for fractions F2 and F3 which had IC50 of 0.42 and 0.51 mg mL−1, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 19 publications
1
19
0
Order By: Relevance
“…Interestingly, all peptides were found novelty identified when compared to previously reported ACE-inhibitory peptides available in the literature. peptides with high ACE-inhibitory capacity [8,38]. Furthermore, actin-derived peptides were found at a percentage of 12 and 10% in SF1 (Fig.…”
Section: Identification Of Bioactive Peptides By Tandem-mass Spectrommentioning
confidence: 89%
See 1 more Smart Citation
“…Interestingly, all peptides were found novelty identified when compared to previously reported ACE-inhibitory peptides available in the literature. peptides with high ACE-inhibitory capacity [8,38]. Furthermore, actin-derived peptides were found at a percentage of 12 and 10% in SF1 (Fig.…”
Section: Identification Of Bioactive Peptides By Tandem-mass Spectrommentioning
confidence: 89%
“…Previous study have shown that ACE-inhibitory peptides from thornback ray muscle hydrolysates were mainly derived from actin (more than 47%) [8].…”
Section: Identification Of Bioactive Peptides By Tandem-mass Spectrommentioning
confidence: 99%
“…Effectively, several researchers groups, have been able to generate various biological activities from different marine proteins in vitro [7][8][9] and in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…ACE‐inhibitory peptides can attach to ACE active site or inhibitor site, which can modify the protein confirmation and prevent from Angiotensin binding to the ACE active site (Wijesekara & Kim, ). Hydrophilic peptides cannot access the active site of ACE (Lassoued et al, ). Considering DPPH scavenging activity of PHP (fractions 62–64 of SEC), fraction eluting at 37 and 32 min showed the highest activity (90.89 and 89.72%).…”
Section: Resultsmentioning
confidence: 99%
“…Hydrophilic peptides cannot access the active site of ACE (Lassoued et al, 2016). Considering DPPH scavenging activity of PHP (fractions 62-64 of SEC), fraction eluting at 37 and 32 min showed the highest activity (90.89 and 89.72%).…”
Section: Fractionation and Purification Of Ace-inhibitory And Antiomentioning
confidence: 98%